2015
DOI: 10.3765/salt.v0i20.2557
|View full text |Cite
|
Sign up to set email alerts
|

Gradable epistemic modals, probability, and scale structure

Abstract: The epistemic modals possible, probable, likely, and certain require a semantics which explains their behavior both as modal operators and as gradable adjectives. An analysis of these items in terms of Kennedy & McNally's (2005) theory of gradability suggests that they are associated with a single, fully closed scale of possibility. An implementation using the standard theory of modality due to Kratzer is shown to make incorrect predictions in several domains. However, identifying the scale of possibility with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The tendency to identify certain with the lower end and possible with the high end of a distribution is also compatible with linguistic analyses of at least and at most readings of numbers, discussed in the introduction. Such readings seem to be particularly frequent in interaction with modals (Lassiter, 2010;Musolino, 2004). Our results add to these analyses by showing empirically that the reverse relationship also applies, namely that epistemic modals induce speakers to select numbers in accordance with such readings.…”
Section: The Extremity Preferencesupporting
confidence: 68%
See 1 more Smart Citation
“…The tendency to identify certain with the lower end and possible with the high end of a distribution is also compatible with linguistic analyses of at least and at most readings of numbers, discussed in the introduction. Such readings seem to be particularly frequent in interaction with modals (Lassiter, 2010;Musolino, 2004). Our results add to these analyses by showing empirically that the reverse relationship also applies, namely that epistemic modals induce speakers to select numbers in accordance with such readings.…”
Section: The Extremity Preferencesupporting
confidence: 68%
“….5 would more accurately be described as likely (Yalcin, 2010). Lassiter (2010) has shown that these three epistemic modals (certain, probable/ likely, and possible) span an underlying "totally closed" scale (i.e., a scale with definite lower and upper bounds; cf. Kennedy & McNally, 2005), similar to the metric (0, 1) probability scale.…”
Section: Suggestions From Linguisticsmentioning
confidence: 99%
“…'Gauzner-Michl is more likely to be the murderer than Kastenjakl. ' Lassiter (2010Lassiter ( , 2011Lassiter ( , 2014Lassiter ( , 2017ab) and Villalta (2008), among others, explicitly model modal meanings using abstract scales. Lassiter 2010, following Yalcin (2010), proposes a model of English gradable epistemic modals like possible and likely in which they are associated with a scale of numerical probabilities.…”
Section: Gradability and Modalitymentioning
confidence: 99%
“…goodness, leaving open the possibility that multiple worlds could 24. Lassiter (2010) argues that distinctions in scale type (described as open versus closed scales by Kennedy and McNally 2005 in the context of gradable adjectives) are relevant to an analysis of gradable epistemic modals. Logoori kudoka is not sensitive to distinctions in scale type, so we do not discuss these differences in our paper.…”
Section: Gradability and Modalitymentioning
confidence: 99%
“…40 By contrast, versions of this argument pattern involving epistemic comparatives like more probable and at least as likely aren't unrestrictedly valid. See Yalcin (2010); Lassiter (2010Lassiter ( , 2017; Holliday & Icard (2013) for discussion. 41 I assume here that valid (deductively good) inferences preserve support.…”
Section: Notesmentioning
confidence: 99%